A matrix-based method for the structural analysis of diagrid systems. (15th August 2019) - Lacidogna, Giuseppe; Scaramozzino, Domenico; Carpinteri, Alberto
Highlights: A matrix-based method (MBM) for the structural analysis of diagrid systems is proposed. The global structure stiffness matrix is directly computed, differently from FEM approach. Two-dimensional as well as three-dimensional diagrid structures can be analysed. To show the method capabilities, the analysis of Swiss Re Tower is performed. The distribution of lateral actions between an external diagrid system and a central core is investigated. Abstract: Diagrid systems have been frequently employed in the last few decades for the construction of tall buildings because of their high lateral stiffness and for their capability to realize complex-shaped structures. Considering mainly diagrid structures with regular forms, many researchers have developed different methods to perform the structural analysis. In this paper, a matrix-based method (MBM) for the analysis of generic freeform diagrid systems is proposed. Unlike existing methodologies, that take into account only shear and bending stiffness, and Finite Element Method approach, the proposed procedure is based on the direct calculation of the complete structure stiffness matrix, without the assemblage of local sub-matrices. This method allows to solve automatically the structural problem, providing both the structure displacements and the axial forces in the diagonals. Then, some comparisons with the Finite Element Method are reported, both for two-dimensional and three-dimensional diagrid systems. In order to show the method capabilities, the analysis concerning the Swiss Re Tower in London is performed. Finally, an application of the MBM is shown regarding the distribution of lateral actions between an external diagrid system and a central core, according to the General Algorithm theory.